Blood Profile of Tilapia (Oreochromis niloticus) Strains Sultana, Nirwana and Larasati against Aeromonas hydrophyla infection - Muhammad Nurhafid; Rima Oktavia Kusuma; Muhammad Sulaiman Dadiono; Kasprijo Kasprijo (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
Aeromonas hydrophyla is a gram negative bacteria, which often infects tilapia and causes internal damage to the liver, spleen and kidneys. Tilapia Sultana, Nirwana and Larasati are superior strains that have fast growth and are resistant to disease. This study was conducted to observe and compare the physiological response of the three strains to Aeromonas hydrophyla infection through blood profiles. The blood profile can describe the health status of the fish. The parameters of the blood profile observed were the number of erythrocytes, hemoglobin, hematocrit, blood glucose, lymphocytes and monocytes. The results showed that the erythrocytes, monocytes and polymorphonuclear counts of the three strains were significantly different, while for hemoglobin, hematocrit, glucose, and lymphocytes were not significantly different.